Misi Perdamaian PBB Dalam Penanganan Konflik: Studi Kasus Peran UNAMID Dalam Pencapaian Resolusi Konflik Darfur Tahun 2007-2011 - Saragih, Andika Amrija (Global and Policy Journal of International Relations, 2016)
ABSTRACTThis research based on the condition of international peace and security that experiencing dynamic and volatile in many parts of the world. A conflict that paid international attention over the past 20 years is the Darfur conflict within the problem of ethnic background. The Darfur conflict has killed at least more than 500,000 people and left more than 750,000 residents to flee to other countries for reasons of security and a better life. Facing the fact that many people who become casualties in this protracted conflict, many international parties are urging the Sudanese government to immediately resolve its internal conflicts and offer help if needed. One of the international organization that assist handling of this conflict is the United Nations (UN). Through the Security Council, the UN established a peacekeeping operation called UNAMID which is a joint mission of peace between the United Nations and the African Union. This peace mission who handle the Darfur conflict to UNAMID managed to achieve a resolution of the conflict in the form of a peace agreement, called the Doha Document for Peace in Darfur in 2011.Keywords : Darfur, UNAMID, conflict resolution, facilitator, peace agreementDOI : https://doi.org/10.33005/jgp.v4i01.1922